Evaluating the Morphometric Characteristics and Water Flow Influences in the Boussaada Wadi Sub-Basin, Algeria: a GIS-Based Approach - Khoudour, Djamel; Bensefia, Sofiane (Ateliê Geográfico, 2025)
The importance of water as a vital resource and development factor is well known all over the world, and its conservation has led to the assessment of morphometric parameters that play an important role in the flow of surface waters. This study emphasizes the morphological analysis of the Wadi Boussaada sub-basin in Algeria, leveraging Geographic Information Systems (GIS) to enhance the understanding of its hydrological dynamics. The watershed and its geomorphological and hydrometric characteristics were identified using a digital terrain model (DTM) derived from SRTM images with a 30-meter resolution. These data were utilized to generate detailed cartographic representations in GIS (ArcGIS), aiding in the development of morphometric databases (BD), geographic, and thematic models. The application of GIS facilitates the extraction of the hydrographic network and sub-watersheds, enabling the calculation of physical watershed characteristics such as shape, relief, and network structure. The study produces thematic maps—including slope, flow direction, and drainage maps—that aid in identifying potential hazard areas within the basin. This approach underscores the importance of morphological analysis while illustrating how GIS can enhance the evaluation process.